Comparison of Random Forest, XGBoost, and LightGBM Methods in Estimating Airbnb Accommodation Rental Prices Based on Customers in New York City - Tauryawati, meylista (Indonesian Journal of Mathematics and Applications, 2023)
The research data was taken from a dataset provided by Inside Airbnb, and the analysis was conducted using machine learning techniques with Random Forest, XGBoost, and LightGBM algorithms. The research stages include data understanding, data preprocessing, data analysis, modeling, model evaluation, and rental price estimation. It is expected that the results of this study can help customers estimate the rental price of Airbnb rooms.